Unusual neutrophilic morphology in influenza-A-induced septic shock: Blue-green inclusions and phagocytosis of autologous cells in a toddler - Wang, Xiaomei; Ma, Xiang; Zeng, Ye; Li, Changzhen (Frontiers in Cellular and Infection Microbiology, 2025)
Influenza A virus is a major cause of seasonal respiratory illness, typically self-limiting in children. However, in rare instances, it can lead to fulminant systemic complications such as acute necrotizing encephalopathy (ANE), sepsis-induced shock, and multiple organ dysfunction syndrome (MODS). We report a rare case of a 2-year-3-month-old girl who developed sepsis-induced shock secondary to influenza A infection. The patient presented with sudden high fever, frequent seizures, impaired consciousness, and respiratory failure. Rapid clinical deterioration ensued, with evidence of profound hyperinflammatory response, coagulopathy, hepatic and myocardial injury, and lactic acidosis. Neurophysiological findings were consistent with ANE. Notably, peripheral blood smear revealed two rare hematologic features: blue-green neutrophilic inclusions (BGNIs) and neutrophilic phagocytosis of both lymphocytes and erythrocytes. These findings—unprecedented in the context of pediatric influenza A infection—may reflect severe immune dysregulation and oxidative stress. Despite aggressive multidisciplinary interventions, the patient succumbed to MODS and disseminated intravascular coagulation (DIC) on day 4 of illness. This is the first reported pediatric case of influenza A infection with concurrent BGNIs and neutrophilic hemophagocytosis in peripheral blood. These morphological abnormalities may serve as hematological markers of life-threatening systemic inflammation in viral sepsis. Awareness and prompt recognition of these features may aid in prognostication and clinical decision making for critically ill children with influenza.